Uncovering the Moderating Role of Locus of Control on the Impact of Training and Development, Organizational Culture, and Leadership Style on Employee Achievement Motivation - Daryawati, Daryawati; Fauzi, Achmad; Satrian, Lini; Setyarini, Lisa Ayu (Dinasti Publisher, 2025)
This study aims to uncover the hidden moderating effect of external locus of control in employees, which weakens the role of training and development, organizational culture, and work environment in supporting high achievement motivation. A total of 120 employees from the Department of Animal Husbandry and Forestry were involved in this study. Data was collected through a questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) analysis. The findings of this study highlight that locus of control (eLOC) has been proven as a moderator in the relationship between training and development, organizational culture, and work environment on employees' achievement motivation. The impact of training and development, organizational culture, and work environment on achievement motivation weakens for employees with a high external locus of control. For employees with a low external locus of control (indicating a high internal locus of control), good training and development, organizational culture, and work environment have a strong potential to enhance their motivation for achievement. However, employees with a high external locus of control tend to rely more on sycophantic behavior, bribery, or currying favor with their superiors to advance in their careers, believing that their career progression is determined by their superiors rather than their own abilities or performance.